2023
DOI: 10.3390/mi14020341
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thin Wall Milling Ability Using Disc Cutters

Abstract: In some cases, industrial practice requires the production of walls or parts with a thickness of less than one millimeter from a metal workpiece. Such parts or walls can be made by milling using disc cutters. This machining method can lead to the generation of residual stresses that determine the appearance of a form deviation characterized by bending the part or the thin wall. To evaluate the suitability of a metallic material for the manufacturing of thin walls by milling with disc cutters, different factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…The adequacy of the empirical mathematical model to the experimental results was assessed using the Gauss criterion. [4,5] Through the mathematical processing of the experimental results and by using the Gauss criterion, it was found that the most appropriate mathematical model is an exponential function of the form: p ac = 74.961 ⋅ 1.007 s 0.999 f (1) the value of Gauss's criterion being S G = 110.075. Since power function mathematical models are often used in manufacturing engineering, such a model was also determined, the form of which is as follows:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The adequacy of the empirical mathematical model to the experimental results was assessed using the Gauss criterion. [4,5] Through the mathematical processing of the experimental results and by using the Gauss criterion, it was found that the most appropriate mathematical model is an exponential function of the form: p ac = 74.961 ⋅ 1.007 s 0.999 f (1) the value of Gauss's criterion being S G = 110.075. Since power function mathematical models are often used in manufacturing engineering, such a model was also determined, the form of which is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…The adequacy of the empirical mathematical model to the experimental results was assessed using the Gauss criterion. [ 4,5 ] Through the mathematical processing of the experimental results and by using the Gauss criterion, it was found that the most appropriate mathematical model is an exponential function of the form: pacbadbreak=0.33em74.961·1.007s0.999f$$\begin{equation}{{p}_{{\mathrm{ac}}}} = \ 74.961 \cdot {{1.007}^s}{{0.999}^f}\end{equation}$$the value of Gauss's criterion being S G = 110.075. Since power function mathematical models are often used in manufacturing engineering, such a model was also determined, the form of which is as follows: pacbadbreak=0.33em3786.863s0.3260.33emf0.585$$\begin{equation}{{p}_{{\mathrm{ac}}}} = \ 3786.863{{s}^{0.326}}\ {{f}^{ - 0.585}}\end{equation}$$for which the value of Gauss's criterion is S G = 90.95158.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations